Numerical Investigation of In-Cylinder Flow Characteristics of Hydrogen-Fuelled Internal Combustion Engine - Hamada, Khalaf I.; M. M., Rahman; D., Ramasamy; M. M., Noor; K., Kadirgama (Universiti Malaysia Pahang, 2016)
This paper addresses the computational fluid dynamics (CFD) simulation to investigate the in-cylinder flow characteristics of 2D combustion chamber for a hydrogen-fuelled four-stroke internal combustion engine. CFD simulation has been carried out using commercial CFD codes. The engine speed was varied from 1000 to 3000 rpm, the range of equivalent ratio from 0.6 to 1.0 and the crank angle from 0 to 720 degrees in this study. The effect of the engine speed and equivalence ratio on the flow-field characteristics and volumetric efficiency are investigated in the motoring condition. The increase of engine speed gives a more efficient diffusion process for hydrogen and gives a more homogeneous air–fuel mixture structure. The characteristics of the flow-field are represented by the in-cylinder pressure and temperature distribution as well as the contours of the hydrogen mass fraction for different engine speeds. The acquired results show the maximum in-cylinder temperature and pressure obtained of 650 K and 1.143 MPa at the engine speed of 3000 rpm respectively. It can be seen that the engine speed and equivalence ratio are strongly related to the volumetric efficiency. The results show that the volumetric efficiency increases linearly with increase of the engine speed, but decreases with increase of the equivalence ratio. The results obtained from the simulation can be employed to examine the homogeneity of the air–fuel mixture structure for a better combustion process and engine performance.